2017
DOI: 10.7557/1.6.1.4096
|View full text |Cite
|
Sign up to set email alerts
|

A binary approach to Spanish tense and aspect: on the tense battle about the past

Abstract: ABSTRACT. The present paper aims at accounting for the Spanish Imperfecto, Perfecto, Pluscuamperfecto and the Indefinido by applying three binary tense oppositions: Present vs Past, Synchronous vs Posterior and Imperfect(ive) vs Perfect(ive). For the sixteen Spanish tense forms under analysis a binary approach leads to covering twelve of them. Their relation with the preterital forms outside the range of the three oppositions is accounted for by two surgical operations: (a) the notion of Imperfect(ive) is seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…We have shown that it is being used in flawless perfect readings (like for example resultative and relevance of the present contexts). As González and Verkuyl (2017) argue, "it is simply occupying the place of the Perf tense form by taking over its role in the binary system" (2017:133). But there is also variation within the Latin American dialects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that it is being used in flawless perfect readings (like for example resultative and relevance of the present contexts). As González and Verkuyl (2017) argue, "it is simply occupying the place of the Perf tense form by taking over its role in the binary system" (2017:133). But there is also variation within the Latin American dialects.…”
Section: Discussionmentioning
confidence: 99%
“…The original construction habere + Participle in Classical Latin initiated a grammaticalization process in Vulgar Latin, and gained new meanings in Romance Languages. González and Verkuyl (2017) discuss the difference between the Spanish Pret canté as a tense form derived from the synthetic Latin Present Perfect cantavi, and the form he cantado as an analytical form which developed from habeo cantatum. These long-term processes that took place in Romance languages have been extensively studied by Harris (1982), Pinkster (1987), Salvi (1987), Bichakjian (1988), Vincent (1988), Schwegler (1990), Ledgeway (2012) and Cennamo (2018), among others.…”
Section: Grammaticalization Of the Perfectmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, this study shows how important it is to include the Present Perfect data in future research. The Present Perfect form is taking over perfective meanings in many languages (González & Verkuyl, 2017) and as a 'new Preterit' it needs to be included in any study investigating the use of past tenses. Its inclusion is even more important for languages such as Dutch and Spanish, where the Present Perfect is advancing in its grammaticalization path toward past tense meanings (Bybee, 1994;González & Verkuyl, 2017;Schwenter, 1994).…”
Section: Discussionmentioning
confidence: 99%